Contextualising Smiles: Is Perception of Smile Genuineness Influenced by Situation and Culture?. (March 2020) - Mui, Phoebe H. C.; Gan, Yangfan; Goudbeek, Martijn B.; Swerts, Marc G. J.
Considerable evidence for contextual effects in emotion perception has been reported, but little is known about how contexts influence the perception of smiles, a rich source of social information. We investigated whether the perceived genuineness of a smile depends on the valence of the situation accompanying the smile, and whether such contextual effects depend on culture. Seventy-two North Americans and 83 mainland Chinese rated the genuineness of smiles displayed by Caucasians and East Asians in three situational contexts (positive, negative, and in isolation). Smiles in a negative situation were considered less genuine than the same smiles rated in isolation; this effect was observed for both groups of observers but stronger for North Americans, a finding at odds with the notion that East Asians are more likely to engage in holistic perceptual processes. Our study demonstrates contextual effects in assessment of smile genuineness, contributing new insights into the perception of affective information.